KU124 (9,10,10-trioxo-N-(2-phenylphenyl)thioxanthene-3-carboxamide) as a novel inhibitor of TASK-1 - Dumani, Ana; Jacob, Annette; Chavez, Diego; Amankwaa, Abena; Zahed, Ramish; Julemis, Martha; Patel, Hinaben; Lopez, Joana; Almazan, Steven; Martins, Patrick; Contreras, Anthony; Korotka, Sofiia; et al. (Frontiers in Pharmacology, 2025)
TASK-1 is a two-pore K+ leak channel. The name, TASK-1, stands for TWIK-related acid-sensitive potassium channel 1, and this channel is encoded by the KCNK3 gene. TASK-1 channels are expressed in humans and modulate cell excitability in excitable cells such as neurons, cardiomyocytes, and vascular smooth muscle cells. TASK-1 inhibition is a mechanism of action for some respiratory stimulants, such as doxapram. TASK-1 channels have also been suggested to play a role in circumventing cell apoptosis in a population of non-small-cell lung cancer cells. We propose that the inner vestibule of the TASK-1 channel, a known binding site of known TASK-1 inhibitors, BAY10000493 and BAY2341237, can be exploited via virtual screening to find other novel TASK-1 inhibitors. Our results show that by targeting the inner vestibule site, we found an active TASK-1 inhibitor. We suspect that this region of interest can be further exploited to discover additional TASK-1 inhibitors. Our initial success lends validity to our virtual screening methodology and parameters. In this study, we identified a novel TASK-1 inhibitor, KU124, which we verified using an in vitro assay.